2018
DOI: 10.1088/1674-1056/27/6/060303
|View full text |Cite
|
Sign up to set email alerts
|

Quantum estimation of detection efficiency with no-knowledge quantum feedback

Abstract: We investigate that no-knowledge measurement-based feedback control is utilized to obtain the estimation precision of the detection efficiency. For the feedback operators that concern us, noknowledge measurement is the optimal way to estimate the detection efficiency. We show that the higher precision can be achieved for the lower or larger detection efficiency. It is found that no-knowledge feedback can be used to cancel decoherence. No-knowledge feedback with a high detection efficiency can perform well in e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…There are two measurement strategies: one is the simultaneous estimation of the two temperatures, the other is the individual estimation of the two temperatures. A lot of works [29][30][31][32][33][34][35][36][37][38] clearly showed that the simultaneous estimation can be more precise than the individual estimation given by the same resource. And then we're going to look at whether that's true in the diffraction case.…”
Section: Estimating Two Different Temperaturesmentioning
confidence: 99%
“…There are two measurement strategies: one is the simultaneous estimation of the two temperatures, the other is the individual estimation of the two temperatures. A lot of works [29][30][31][32][33][34][35][36][37][38] clearly showed that the simultaneous estimation can be more precise than the individual estimation given by the same resource. And then we're going to look at whether that's true in the diffraction case.…”
Section: Estimating Two Different Temperaturesmentioning
confidence: 99%
“…If multiple observation operators need to be measured at the same time, the above equation can be extended to [45] dρ(t) dt…”
Section: Investigation Modelmentioning
confidence: 99%
“…Once the backaction is perfectly reversed for all individual noise realizations, the decoherence on the system's average dynamics can be completely suppressed. The protocol can be applied in the case where the system-bath coupling operators are Hermitian, but can also be adapted for non-Hermitian coupling by adding extra conjugate channels (e.g., using gain and loss channels for bosonic baths) and mixing output records using beam splitters [15,18,19].…”
Section: Introductionmentioning
confidence: 99%